Assessing the Influence of Type of Base Materials on Choosing Permanent Restoration in Pulp Capping - A Retrospective Analysis - R, KEERTHIKA.; SHARMA, SUBASH; SUGUMARAN, SURENDAR (The journal of contemporary issues in business and government, 2021)
The success of vital pulp therapy techniques is considerably dependent on the technique employed,the inflammatory status of the pulp tissue,the type of pulp therapy agent used and period of observation. The commonly used agents are calcium hydroxide ,Resin modified glass ionomer cement and mineral trioxide aggregate. The permanent restoration following the pulp capping plays a very crucial role in the success of the treatment. The commonly used restorations are composites,amalgam and bilayered restoration.The aim of this study was to assess the type of base materials in pulp capping and its influence on permanent restoration.A cross sectional study done at Saveetha Dental College with the sample size of 69 was analysed. The factors like age ,gender,base material ,type of teeth and permanent restoration were assessed. The P value of less than 0.05 was considered to be significant.Result of type of base material showed,Calcium hydroxide >Calcium hydroxide +Resin modified glass ionomer cement >Bio aggregate material and the permanent restoration showed Composite >Bilayered restoration > Amalgam.The statistical analysis showed the p value =0.338( >0.05) ,which implies that there is no significant association between the type of base material with the type of permanent restoration.The current study showed that calcium hydroxide and composite restoration were the preferred options of base material and permanent restoration respectively.But with recent advances it has been proved that Bioaggregate material has better properties than calcium hydroxide ,which is no longer a gold standard material.